Women and ICTs: Perception and attitude - Okello, Dorothy (Technical Centre for Agricultural and Rural Cooperation, 2012)
Women's access to ICTs has grown during the last decade. However, there remains a need to address affordability and the perception and attitude towards the use of ICTs by women.